2016
DOI: 10.1021/acssuschemeng.6b00455
|View full text |Cite
|
Sign up to set email alerts
|

Acrylic Triblock Copolymers Incorporating Isosorbide for Pressure Sensitive Adhesives

Abstract: A new monomer acetylated acrylic isosorbide (AAI) was prepared in two steps using common reagents without the need for column chromatography. Free radical polymerization of AAI afforded poly­(acetylated acrylic isosorbide) (PAAI), which exhibited a glass transition temperature (T g) = 95 °C and good thermal stability (T d, 5% weight loss; N2 = 331 °C, air = 291 °C). A series of ABA triblock copolymers with either poly­(n-butyl acrylate) (PnBA) or poly­(2-ethylhexyl acrylate) (PEHA) as the low T g midblocks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
120
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 37 publications
5
120
0
Order By: Relevance
“…This different stereoisomer structure leads to different reactivity of each hydroxyl group in the endo ‐ and exo ‐form, because of the intramolecular hydrogen bonding between the endo ‐form hydroxyl group and oxygen atom in the bicyclic ether core . A few synthetic methods to introduce methacrylate into isosorbide using methacrylic anhydride with the stoichiometric equivalent of an NH 3 base, or methacryloyl chloride with an equivalent of Et 3 N have been reported in the literature . Meanwhile, in an attempt to obtain enantioselective product of ISA bearing one free hydroxyl group through a one‐pot reaction, we carefully synthesized ISA at low temperature and with slow dropwise rate controlled by a syringe pump.…”
Section: Resultsmentioning
confidence: 99%
“…This different stereoisomer structure leads to different reactivity of each hydroxyl group in the endo ‐ and exo ‐form, because of the intramolecular hydrogen bonding between the endo ‐form hydroxyl group and oxygen atom in the bicyclic ether core . A few synthetic methods to introduce methacrylate into isosorbide using methacrylic anhydride with the stoichiometric equivalent of an NH 3 base, or methacryloyl chloride with an equivalent of Et 3 N have been reported in the literature . Meanwhile, in an attempt to obtain enantioselective product of ISA bearing one free hydroxyl group through a one‐pot reaction, we carefully synthesized ISA at low temperature and with slow dropwise rate controlled by a syringe pump.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing with the direct use as a diol and cross-linking monomer, mono-vinyl isosorbide derivatives have been reported only in a few works of literature. [26][27][28][29][30][31][32] These mono-vinyl isosorbide monomers are especially useful and could nd important applications in the construction of polymers with designed architectures through chain-growth polymerizations. For example, Beghdadi et al 31 reported that the substitution of the vinyl triazole moiety at either the endo-or exo-position had a signicant effect on the glass transition temperature T g and solubility of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…For RAFT polymerization, utilization of specific chain‐transfer agent (CTA) which can form a dormant species during the polymerization process allows production of polymer products with controlled molecular weight and narrow molar mass dispersity ( Đ ). With proper CTAs, synthesis of homopolymers, block copolymers and polymers with various architectures, such as star, macrocycle, hyperbranch and comb, can be achieved . Until now, most of RAFT polymerizations were performed with batch to batch reaction on a relatively small scale.…”
Section: Introductionmentioning
confidence: 99%